2005
DOI: 10.1111/j.1745-7254.2005.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MePEG molecular weight and particle size on in vitro release of tumor necrosis factor-alpha-loaded nanoparticles1

Abstract: Aim: To study the in vitro release of recombinant human tumor necrosis factor‐alpha (rHuTNF‐α) encapsulated in poly (methoxypolyethyleneglycol cyanoacrylate‐co‐n‐hexadecyl cyanoacrylate) (PEG‐PHDCA) nanoparticles, and investigate the influence of methoxypolyethyleneglycol (MePEG) molecular weight and particle size. Methods: Three sizes (approximately 80, 170, and 240 nm) of PEGPHDCA nanoparticles loading rHuTNF‐α were prepared at different MePEG molecular weights (Mr=2000, 5000, and 10 000) using the double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…It could be attributed to the adsorption of released insulin onto nanoparticles. A similar phenomenon has already been observed by other groups (Quellec et al, 1998;Zambaux et al, 1999;Fang, Shi, & Pei, 2005). In our case, it was only observed for conventional particles.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It could be attributed to the adsorption of released insulin onto nanoparticles. A similar phenomenon has already been observed by other groups (Quellec et al, 1998;Zambaux et al, 1999;Fang, Shi, & Pei, 2005). In our case, it was only observed for conventional particles.…”
Section: Discussionsupporting
confidence: 88%
“…Although there was a burst for both types of insulinloaded nanoparticles, it appeared that the presence of LMWH increases this effect; insulin was more rapidly released from Stealth insulin-loaded nanoparticles than from conventional nanoparticles: the initial release at 5 min was 62%, followed by a constant and slow release (up to 70%) at 24 h. In the case of S-INP, the very hydrophilic LMWH chains at the surface of the particles facilitate the penetration of the dissolution aqueous medium into the nanoparticles. Indeed, it was already demonstrated that the more hydrophilic the surface of particles, the faster the burst for a hydrophilic drug (Fang, Shi, & Pei, 2005;Liu et al, 2007). At the pH of the dissolution medium (pH 7.4), insulin was negatively charged.…”
Section: Discussionmentioning
confidence: 98%
“…Results from this study suggest that PEGylation of c-T 3 represents 47 a viable platform for the oral and parenteral delivery of c-T 3 for potential use in the prevention of breast 48 cancer. 49 Ó 2015 Published by Elsevier B.V. 50 51 52 53 1. Introduction 54 Vitamin E from palm oil refers to a family of eight related, lipid 55 soluble, compounds that are divided into two subfamilies known 56 as tocopherols (T) and tocotrienols (T 3 ).…”
mentioning
confidence: 99%
“…According to the Stokes-Einstein equation, decreasing the NP size leads to an increase in the diffusion coefficient, making it easier for smaller particles to penetrate through the mucus 13 . However, small NPs with high surface areas exhibit burst effects, which lead to poor efficacy at the targeted tissues 17 . Moreover, extremely small NPs (2-10 nm) would yield inefficient cellular uptake 18,19 .…”
mentioning
confidence: 99%